Annulment of Marriage and Khuluk in Family Law in Muslim Countries: A Comparative Study of Family Law in Syria, Sudan, Turkey and Indonesia - Abdul Hakim (Alhurriyah, 2022)
This research discusses the renewal of family law which regulates marriage, child-rearing, inheritance, and so on in several Muslim countries. In line with the times, countries, where the majority of the population is Muslim, have begun to reform their respective country's legal systems, both criminal law, and civil law. The research in this article aims to determine the comparison of one country to another according to the level of secular, liberal, or viewed from another side in efforts to reform family law. The research in this article is qualitative research using the literature study method. The research in this article uses a comparative and historical approach. Sources of data in this study are legal products of Islamic countries, scientific journals, and other supporting documents. The research in this article finds that Syria and Sudan are examples of Islamic countries that still maintain Islamic law and its values in their laws and regulations. Meanwhile, Turkey has gone far beyond Islamic law and adopted Western legal standards. Indonesia did not adopt Islamic law as a whole and also did not adopt Western law as a whole.